1986
DOI: 10.1530/jrf.0.0770381
|View full text |Cite
|
Sign up to set email alerts
|

Proteins secreted by Day-16 to -18 bovine conceptuses extend corpus luteum function in cows

Abstract: Summary. Corpus luteum function, interoestrous interval and spontaneous uterine PGF-2\g=a\ (PGF) production were evaluated in 9 cyclic Holstein cows (3/group) after intrauterine injections of pooled conceptus secretory proteins, 5\g=b\-pregnan-3\g=a\-ol -20\x=req-\ one, or homologous serum proteins on Days 15\m=.\5 through 21 after oestrus. A significant extension of corpus luteum lifespan and interoestrous interval were detected in cows treated with conceptus secretory proteins compared to the other 2 groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
7

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(74 citation statements)
references
References 30 publications
(37 reference statements)
4
63
0
7
Order By: Relevance
“…Our hypothesis that prostaglandin substrate may be diverted from PGF to other prostaglandins is, therefore, incorrect. In sheep and cattle, intrauterine infusion of secretory proteins from the early conceptus extends the length of dioestrus Knickerbocker et al, 1986;Vallet et al, 1988). Measurement of prostaglandin concentrations revealed that these proteins inhibited endometrial synthesis of PGF but not of PGE-2 (Vallet et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis that prostaglandin substrate may be diverted from PGF to other prostaglandins is, therefore, incorrect. In sheep and cattle, intrauterine infusion of secretory proteins from the early conceptus extends the length of dioestrus Knickerbocker et al, 1986;Vallet et al, 1988). Measurement of prostaglandin concentrations revealed that these proteins inhibited endometrial synthesis of PGF but not of PGE-2 (Vallet et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The blood samples were refrigerated at 4°C for 24h and then centrifuged (1200 x g for 15 minutes) for separation of serum. Serum was frozen and stored at -20 º C until radioimmunoassay for P4 determination (Knickerbocker et al, 1986 performed and intra-assay coefficients of variation were 7.6, 8.2, and 5.3, with inter-assay coefficient of variation of 7.9 and assay sensitivity of 0.3ng/ml.…”
Section: Methodsmentioning
confidence: 99%
“…The intra-and inter-assay coefficients of variation were 4.2 and 7.5%, respectively. Plasma concentrations of progesterone were measured in a single assay using procedures described previously (Knickerbocker et al, 1986). Intra-assay coefficient of variation was 6%.…”
Section: Introductionmentioning
confidence: 99%